Emotional overeating is common and negatively associated with alcohol use in normal-weight female university students. (1st October 2018) - Constant, Aymery; Gautier, Yentl; Coquery, Nicolas; Thibault, Ronan; Moirand, Romain; Val-Laillet, David
Abstract: introduction: Eating in response to specific emotional cues was hitherto investigated in relation to weight gain, eating disorders, and psychiatric and addictive disorders. Given the difficulties in treating established obesity, preventive interventions towards normal-weight subjects could be more appropriate and cost effective. In order to design such interventions, it is important to characterize emotional overeating in normal-weight subjects, especially young women. Methods: Female university students aged 18–24 years with healthy Body Mass Index (comprised between 18.5 and 24.9) were asked to complete questionnaires while attending a medical consultation. Emotional Eating frequency in the last 28 days was assessed together with data on habitual physical activity, drinking patterns, substance abuse, suspected eating disorders and cognitive/behavioural components of eating. Sociodemographic data and tobacco use were also collected. Results: Half of participants reported intermittent Emotional Overeating in the last 28 days, mostly during one to five days in the last 28 days, in response to Anxiety (51.3%), Loneliness (45.1%), Sadness (44.8%), and Happiness (43.6%), and to a lesser extent in response to Tiredness (27.4%) and Anger (14.6%). In multivariate analysis, Distress-Induced Overeating (DIO) correlated positively with inability to resist emotional cues, disordered eating symptoms, and loss of control over food intake. It correlated negatively with moderate and excessive drinking. Conclusion: A large proportion of normal-weight female students used intermittent overeating episodes as a time-limited response to emotional states, especially anxiety. DIO was negatively correlated with alcohol use, which suggests two distinct and somewhat exclusive ways of coping with negative emotions. It was higher in the minority of students with disordered eating symptoms and loss of control over food intake, highlighting the need for a systematic screening in all female students entering college.